UPLC/Q-TOFMS-Based Metabolomics Approach to Reveal the Protective Role of Other Herbs in An-Gong-Niu-Huang Wan Against the Hepatorenal Toxicity of Cinnabar and Realgar - Xia, Fangbo; Li, Ao; Chai, Yushuang; Xiao, Xiao; Wan, Jianbo; Li, Peng; Wang, Yitao (Frontiers in Pharmacology, 2018)
An-Gong-Niu-Huang Wan (AGNH) is a well-known traditional Chinese medicine (TCM) recipe containing cinnabar (HgS) and realgar (As2S2). However, the application of AGNH is limited by the hepato- and nephrotoxicity of cinnabar and realgar. It should be noted that cinnabar and realgar in AGNH are not used alone, but rather combined with other herbs as formula to use. In this study, the protective effects and mechanisms of the other herbs in AGNH against the hepatorenal toxicity induced by cinnabar and realgar were investigated. The combination use of the other herbs in AGNH alleviated inflammatory cell infiltration and damage in the liver and kidney and restored the disturbed serum metabolic profile induced by cinnabar and realgar insults. By UPLC/Q-TOFMS combined with pattern recognition approaches, we identified 41 endogenous metabolites in the sera of mice that were related to the hepatorenal toxicity of cinnabar and realgar, 36 of which were restored to normal levels when various kinds of herbs were combined as compound recipe. These metabolites function as modulators in inflammation-associated glycerophospholipid, arachidonic acid, linoleic acid, sphingolipid and ether lipid metabolic pathways. Notably, lysophosphatidylcholines (LysoPCs) were the most elevated among all of the metabolites detected after cinnabar and realgar treatment, while these LysoPCs did not show overt differences between the AGNH and saline control groups, which was associated with relatively unaffected or even up-regulated expression of lysophosphatidylcholine acyltransferase 1 (LPCAT1) and autotaxin (ATX). These findings indicated that other herbs in AGNH could have a protective effect against cinnabar- and realgar-induced hepatic and renal damage via modulating the disordered homeostasis of the glycerophospholipid, arachidonic acid, linoleic acid, ether lipid and sphingolipid metabolism.